Advanced Chromatic Dispersion Compensation in Optical Fiber FBMC-OQAM Systems - Francois Rottenberg; Trung-Hien Nguyen; Simon-Pierre Gorza; Francois Horlin; Jerome Louveaux (IEEE Photonics Journal)
We report on several methods for the chromatic dispersion (CD) compensation in optical fiber offset-QAM-based filterbank multicarrier (FBMC-OQAM) systems. We show that several equalization structures, initially proposed for wireless FBMC-OQAM systems, can also be applied to optical FBMC-OQAM systems to enhance the CD tolerance. The different CD compensation algorithms are numerically validated and compared to the conventional one tap equalizer in a 30-Gbaud optical FBMC system, in terms of performance and complexity. Considering a 1-dB optical signal-to-noise ratio penalty at a bit error rate of $3.8× 10^{-3}$ and 256 subcarriers, the results show that the maximum CD tolerance of the frequency spreading method can be enhanced by a factor 10 and 30 for 4-OQAM and 16-OQAM modulations, respectively, compared to that of the conventional one-tap equalizer, at the cost of higher complexity. Even though the other CD compensation methods provide a reduced CD tolerance compared to the frequency spreading method, they require less complexity and hence can be good alternatives.